A dynamic systems theory model for reading motivation among English as a foreign language learners in China (Journal of Applied Learning and Teaching, 2020)
English learning has been prevalent in China since the Reform and Opening-up Policy in the early 1980s. The number of English learners in China has increased tremendously over the years and the approach to learning English as a foreign language has also changed over time. However, most studies on reading motivation were conducted at one point in time rather than discussing it from a dynamic perspective. The article begins with a literature review, then discusses the relationships and interconnections between factors influencing reading motivation, adopting a Dynamic Systems Theory, to develop a conceptual model to study the reading motivation among English as a Foreign Language learners in China.